Digitalisasi pada Proses Verifikasi Tagihan Transaksi Jasa Menggunakan Sistem Informasi Akuntansi PT Petrokimia Gresik - Fitria, Berliana Aini; Raharjo, Yulianti (Forum Kerjasama Pendidikan Tinggi, 2025)
The rapid advancement of information technology has driven the digitalization of various business processes, including service invoice verification. This study aims to evaluate the effectiveness of implementing a web-based accounting information system, the Smart & Intelligent Procurement System (SIPS), in accelerating and streamlining the invoice verification process at PT Petrokimia Gresik. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation during an internship program. The findings indicate that using SIPS improves work efficiency, reduces administrative errors, expedites verification processes, and supports transparency and accountability. The system also enhances interdepartmental coordination and vendor relationships. In conclusion, SIPS represents a successful form of digital transformation that optimizes service invoice verification and supports a more modern and effective administrative management system.